2011
DOI: 10.1002/btpr.649
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and pH on growth and antioxidant content of the microalga Scenedesmus obliquus

Abstract: Reactive forms of oxygen can damage DNA (among other molecules), thus triggering, e.g., atherogenesis and carcinogenesis. However, such dietary antioxidants as lutein and β-carotene can effectively inactivate them; these compounds were found to high levels in a novel strain (M2-1) of the microalga Scenedesmus obliquus. The independent and combined effects of pH and temperature on its rates of growth and production of antioxidants were experimentally assessed, via a full factorial experimental design; the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 32 publications
2
51
0
1
Order By: Relevance
“…Extracellular and intracellular extracts were collected according to Guedes et al [24]. In short, 5 mL of a 30 day-old culture was centrifuged at 4000 rpm, for 7 min at 15 °C, and the supernatant ( i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular and intracellular extracts were collected according to Guedes et al [24]. In short, 5 mL of a 30 day-old culture was centrifuged at 4000 rpm, for 7 min at 15 °C, and the supernatant ( i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Full description of the HPLC procedure is available elsewhere [24,31]; neoxanthin, violaxanthin, lutein, zeaxanthin, and β-carotene were assayed for, owing to their known antioxidant features.…”
Section: Methodsmentioning
confidence: 99%
“…This may be attributed to the presence of antioxidants in the peels [23]. For the peeled samples, both sodium metabisulphite and blanching treatments caused significant reduction in the pH of the flour samples, with the sodium metabisulphite treatment having the greatest pH reducing effect.…”
Section: Slicingmentioning
confidence: 98%
“…Studies also show that antioxidant activities are influenced by illuminance while culturing (Madhyastha et al, 2009). The effect of pH and temperature on antioxidant productivity in Scenedesmus were assessed by Guedes et al (2011) and found that pH plays an important role in antioxidant content. The effect of antioxidants on DPPH free radical scavenging was considered to be due to their hydrogen donating ability.…”
Section: Correlation Between Phenolic Content and Antioxidant Propertmentioning
confidence: 99%